Analisa Perancangan Sistem Rekomendasi Makanan Untuk Defisit Kalori “Calcraft” Melalui Evaluasi UI UX - Putu Ananda Darma Wiguna; Luh Gede Astuti (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2024)
This research raises issues related to unbalanced diets in modern society that cause obesity problems. As a solution, calorie deficit was chosen as a program to solve this obesity problem. Developed an application called